Analisis Determinan Lingkungan Kerja Terhadap Kinerja Tenaga Perawat Di Rumah Sakit Umum Bahteramas Provinsi Sulawesi Tenggara - Rania Fatrizza Pritami; Marheni Fadillah Harun; Fitri Kurniawati; Irman Idrus (LP3M Universitas Muhammadiyah Kendari, 2021)
Hospitals must continue to develop in order to improve the quality of hospital services. The purpose of the study was to determine the relationship between the work environment and job satisfaction of nurses at Bahteramas Hospital, Kendari City. Quantitative research method with cross sectional study approach with relative random sampling technique. Data analysis using Chi-Square test and multiple linear regression analysis. The results showed that there was a relationship between transformational leadership and nurse job satisfaction (p=0.001), structural empowerment and nurse job satisfaction (p=0.001); ideal professional practice with nurse job satisfaction (p = 0.001); innovation with nurse job satisfaction (p=0.013); and empirical quality with nurse job satisfaction (p = 0.017). The conclusion is that the determinant analysis states that there is a relationship between the work environment and job satisfaction of nurses.